Behavior of Light Category Autism Children In Sensorymotor Playing In TK Talenta Semarang - Amalia, Rizki; Windiarti, Rina (BELIA: Early Childhood Education Papers, 2018)
Problem in this research is the behavior of children with autism is different from the behavior of light category children without special needs while it is playing. Sensorymotor ability of autistic children seen by playing sensorymotor. Sensorymotor play to help reveal stimuli through the senses that occur physical relationship with the environment. This study aims to explain the behavior of autistic children in the lightweight category as well as contributing factors sensorymotor play activities of children with autism, light category in TK Talenta Semarang. This research is a qualitative descriptive study and using the method of observation, interviews, and documentation of the data it collects. Determination of informants is purposive sampling informants selected is one parent with a child with autism is the mother, two teachers and three students of the class with children with autism. Data analysis techniques using Miles and Huberman. This research was conducted in TK Talenta Semarang. TK Semarang is an inclusive school that accepts students with various needs of children without any distinction as well as children with autism. The result of this research is the behavior of children with autism in sensorymotor play in TK Talenta Semarang deficient behavior and excessive behavior. Behavior deficient characterized by lack of focuschildren in learning activities, while the excessive behavior characterized by an aggressive child behavior, run-run-off, and hurt others. Factors supporting the activity of sensorymotor play in TK Talenta Semarang is learning very comfortable room for props complete and their students are taught to accept the advantages and disadvantages of his friends. Teacher motivation is very important in the learning process of encouragement contained in a person to try to establish behavioral changes that better meet their needs.